Análise de filtros híbridos aplicados a um forno elétrico a Arco - Soares Junior, Dirceu (2011)
A steelmaking plant is characterized for having in its productive process non linear loads of high power. For these loads, the steelmaking industries called mini-mill normally have Electric Arc Furnace (EAF) in its initial steel production phase that happen with metallic scrap melting being the principal raw material used. The EAF absorb a distorted current from the electric main, causing voltage distortion in its point of common coupling (PCC) and many problems with respects the electric power quality. A standard solution used for the harmonic mitigation in this application is obtained through the use of composite passive filter. However this is a solution that can cause harmonic resonance, increasing the harmonic distortion in the electrical system and causing overload in the filtering system. In this work, a case in a non integrated steel industry, located at Grande Vitoria region, is presented. Through measurements in the main substation of the plant, the main current and voltage waveforms are presented, along with its harmonic spectrum, that confirm the existence of harmonic resonance phenomenon, mainly from Electric Arc Furnace current. The measurement considered in this work to simulate the hybrid filters models, was that originated from operational condition with higher process criticism, under viewpoint of the moment where the behavior of the load brings to a major deviation regarding the power quality at the measured variables. The model used for the system under study shows strong correlation with the real system portrayed through the electrical measurements done. Using the model, a comparative simulation analysis is done, between two hybrid topologies, the series hybrid filter and the parallel hybrid filter, with the objective of harmonic compensation and resonance damping. The results of simulations and resonance analysis showed that the parallel hybrid filter is the topology that allows the greatest reduction in harmonic distortion of current and voltage in the PCC (Point of Common Coupling), using an active filter with the lowest nominal power rating. However, the parallel hybrid filtering does not provide the complete elimination of parallel resonance, and for the series resonance, the filter used does not have the ability to interfere in the harmonic amplification condition existing in the electrical system. Finally, the study proposes that the best filtering alternative takes into account the choice of the active filter gain and consequently its power, so well aligned with the objectives of improving the power quality that are expected for the system under analysis